The world's most popular manga dragon ball : the training of kame-sen'nin - Toriyama, Akira (San Francisco : VIZ Media, 2021)
In a In their search for seven Dragon Balls, Goku and Bulma encounter several obstacles, including the Turtle Hermit, the shapeshifter Oolong, the bandit Yamcha, and the Ox King of Frypan Mountain. In a graphic novel that reveals the early days of the heroes of "Dragon Ball Z."
VOL 3
Keywords: Adventure fiction